Hypothalamic Nesfatin-1 Resistance May Underlie the Development of Type 2 Diabetes Mellitus in Maternally Undernourished Non-obese Rats - Durst, Máté; Könczöl, Katalin; Ocskay, Klementina; Sípos, Klaudia; Várnai, Péter; Szilvásy-Szabó, Anett; Fekete, Csaba; Tóth, Zsuzsanna E. (Frontiers in Neuroscience, 2022)
Intrauterine growth retardation (IUGR) poses a high risk for developing late-onset, non-obese type 2 diabetes (T2DM). The exact mechanism underlying this phenomenon is unknown, although the contribution of the central nervous system is recognized. The main hypothalamic nuclei involved in the homeostatic regulation express nesfatin-1, an anorexigenic neuropeptide and identified regulator of blood glucose level. Using intrauterine protein restricted rat model (PR) of IUGR, we investigated, whether IUGR alters the function of nesfatin-1. We show that PR rats develop fat preference and impaired glucose homeostasis by adulthood, while the body composition and caloric intake of normal nourished (NN) and PR rats are similar. Plasma nesfatin-1 levels are unaffected by IUGR in both neonates and adults, but pro-nesfatin-1 mRNA expression is upregulated in the hypothalamus of adult PR animals. We find that centrally injected nesfatin-1 inhibits the fasting induced neuronal activation in the hypothalamic arcuate nucleus in adult NN rats. This effect of nesfatin-1 is not seen in PR rats. The anorexigenic effect of centrally injected nesfatin-1 is also reduced in adult PR rats. Moreover, chronic central nesfatin-1 administration improves the glucose tolerance and insulin sensitivity in NN rats but not in PR animals. Birth dating of nesfatin-1 cells by bromodeoxyuridine (BrDU) reveals that formation of nesfatin-1 cells in the hypothalamus of PR rats is disturbed. Our results suggest that adult PR rats acquire hypothalamic nesfatin-1-resistance, probably due to the altered development of the hypothalamic nesfatin-1 cells. Hypothalamic nesfatin-1-resistance, in turn, may contribute to the development of non-obese type T2DM.